REVIEWING A NOTARY ETHICS BASED ON ETHICAL CODE AS A NOTARY PROFESSION - Hafid Zakariya; Yuni Purnama Sari; Desty Prabandari; Widha Rahmawati Budiatmaja (Yustisia, 2017)
This paper aimed to find out the responsibilities and sanctions of a notary when a notary violates the existing ethics code.The various rules in the notary profession code of ethics will be attributed to the notary's behavior, so that in carrying out the duties there is a responsibility that must be enforced and  If it contradicts with the ethics code,it will get sanction in accordance with the enactment of the Notary’s Office Law. Because the role of notary in society is important to determine the land deed in Indonesia, we need to understand how the notary in enforcing their ethics as notary profession. The Notary is expected to be neutral, so if placed in one of the three state agencies Judiciary, Executive, and Legislative, the Notary is no longer considered neutral. With the neutral position, notary is expected to provide legal counseling for a legal action by a notaryat the request of client. In the case of taking legal action for client, the notary also may not take side the client, because the duty of a notary is to prevent the occurrence of problems